Characteristics of mobile social media usage and dependence among college students in a Chinese provincial capital city - Liu, Gang (Frontiers in Education, 2025)
This study investigated preferences for mobile social media usage types, frequency and dependence among college students utilizing a questionnaire. Participants were recruited from five universities in a provincial capital in Central China, and data collection was conducted from September to December 2024. The survey recovered a total of 566 valid questionnaires from 288 female and 278 male respondents. Findings indicated that mobile social media have become major channels for students to maintain interpersonal relationships, and most students used two or more mobile social media platforms. A total of 31.25% of students used mobile social media for more than 4–6 h per day. Significantly higher scores for compulsion and conflict variables were detected in females vs. males while mobile social media dependence showed no gender differences. Moreover, the analysis of different grades showed statistically significant differences between lower- and higher-grade students in social gain, conflict and withdrawal but not prominence or compulsion. Analyses stratified by majors indicated statistically significant differences in social gain, compulsion, conflict and withdrawal. The survey also showed that nearly all the students engaged in paid consumption on mobile social media platforms. More than half of the participants believed that mobile social media had a substantially effected their lives, decreased real-life social skills and negatively affected long-term and stable interpersonal relationships. The proliferation of smartphones and mobile social media applications has significantly increased college students' dependency on these platforms. Addressing this reliance requires targeted interventions to promote healthier digital habits.